2017
DOI: 10.1080/14767058.2017.1401996
|View full text |Cite
|
Sign up to set email alerts
|

How does preeclampsia affect neonates? Highlights in the disease’s immunity

Abstract: The cytotoxic environment present in PE affects the development of fetal cell lineages. Neutropenia is observed in 50% of neonates and is correlated with mortality, although its treatment is not well-established. The enhancement in erythropoietin and the hypoxic setting present in the disease can also lead to thrombocytopenia. Per partum management includes platelet transfusion in order to avoid severe complications such as intraventricular hemorrhage. Regarding other cell lines, a cytotoxic profile is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
2
23
1
2
Order By: Relevance
“…Because most stillbirths were encountered in the PE group, we believe this phenomenon could be linked with the fetus’ inability to mount an inflammatory response. Our assertion is supported by previous studies demonstrating that babies of mothers with PE display disrupted hematopoiesis manifested as neonatal thrombocytopenia and neutropenia [53]. Because transcription of the human Hp gene is induced by IL-6, a fetal hypo-inflammatory response would be also associated with low Hp levels and death, as previously shown [50,54].…”
Section: Discussionsupporting
confidence: 88%
“…Because most stillbirths were encountered in the PE group, we believe this phenomenon could be linked with the fetus’ inability to mount an inflammatory response. Our assertion is supported by previous studies demonstrating that babies of mothers with PE display disrupted hematopoiesis manifested as neonatal thrombocytopenia and neutropenia [53]. Because transcription of the human Hp gene is induced by IL-6, a fetal hypo-inflammatory response would be also associated with low Hp levels and death, as previously shown [50,54].…”
Section: Discussionsupporting
confidence: 88%
“…Studies suggest that increased erythropoiesis and reduced white cells are associated with prolonged exposure to hypoxia 20 21 It is suggested that frequent placental infarctions with platelet consumption may lead to thrombocytopenia and polycythemia, and that preeclampsia and chronic hypertension may play a role in the genesis of thrombocytopenia 5 …”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of preeclampsia is not fully known, a proinflammatory immune state prevails and can disrupt fetal hematopoiesis. Some of the effects on newborns include neonatal thrombocytopenia, neutropenia, a reduction in T regulatory cells, and an increased cytotoxic natural killer cell profile [3,4]. There are no established international guidelines for routine screening of babies delivered to women with preeclampsia.…”
Section: Introductionmentioning
confidence: 99%